THE EFFECT OF COLD BREW AND HOT BREW EXTRACTION METHODS AND DURATION OF FERMENTATION ON THE QUALITY OF ROBUSTA COFFEE WINE (Coffea canephora) TEMANGGUNG - Nokabun, Karolus Yubel; Handoko, Yoga Aji (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2024)
This study examines the effect of fermentation duration and extraction methods (cold brew and hot brew) on the quality of robusta wine coffee. Wine coffee is a beverage resulting from the fermentation process of coffee extract which is providing a unique taste with a blend of coffee and alcohol flavors, along with a characteristic wine aroma. Through these two extraction methods, cold brew and hot brew offer different characteristics to the chemical parameters such as pH, reducing sugar content, alcohol content, caffeine content, and flavor. The research results indicate that cold brew yields a lighter flavor, while hot brew tends to have a stronger or more bitter taste. The duration of fermentation significantly affects the chemical parameters, with a decrease in pH and reducing sugar content as fermentation time increases. The alcohol content in cold brew reaches 19.93% on day 28, higher than hot brew which has 18.40% of alcohol. Organoleptic analysis results show that cold brew is preferred by the panelists, especially on the 28th day of fermentation.